The prevalence of dry eye syndrome among patients at the eye clinic in Nelson Mandela Academic Hospital - Nonkula, Doran Monwabisi (University of the Free State, 2019)
Introduction: Dry eye syndrome (DES) is a multi-factorial disease of the tears and ocular surface that results in ocular discomfort, visual disturbance, and tear-film instability with potential damage to the ocular surface. The aim of the study was to determine the prevalence of dry eye syndrome among patients at the Eye Clinic in Nelson Mandela Academic Hospital (NMAH) in Mthatha. No study has been published on the prevalence of dry eye syndrome in the Eastern Cape Province. Method: This is an observational descriptive study that looked at the prevalence of dry eye syndrome among patients at the eye clinic in Nelson Mandela Academic Hospital (NMAH). Dry eye syndrome was assessed using the Ocular Surface Disease Index (OSDI) questionnaire, Tear-Break Up Time (TBUT) and Schirmer 2 Test. The OSDI questionnaire was administered by a trained optical dispenser student to the participants that agreed to partake in the study. Following the completion of the OSDI questionnaire, the three clinical tests were performed in sequence. The researcher used the same slit lamp for all the participants and tests. The researcher started assessing for the Meibomian glands to determine whether the participant had Meibomian gland dysfunction or not. After the assessment of Meibomian glands, the TBUT was measured. The Schirmer 2 test was performed 5 minutes later after the TBUT was performed. When performing the Schirmer 2 test, novesin wander was used as a local anesthetic for all participants. The Schirmer strips were measured with a millimeter ruler after 5 minutes of inserting the strip in the lower lid of each eye. A stopwatch was used for timing when performing the TBUT and Schirmer 2 tests. The outcomes of each test were recorded on the data sheet that was marked uniquely using a code for each participant. Results: One hundred and fifty participants took part in the study, and 72% of the participants were females. The prevalence of dry eye syndrome was determined to be 92.00% when using the OSDI. The OSDI determined the prevalence of severe dry eye syndrome to be 64.67%. The Tear Break-Up Time (TBUT) and Schirmer’s 2 test determined the prevalence of dry eye syndrome to be 64.67% and 62.67% respectively. Conclusion: There was high prevalence of DES among patients at the Eye clinic in NMAH. Females were predominantly affected more than males. An intervention from health authorities is required in order to curb the disease. Eye care personnel, such as Ophthalmic nurses, Optometrists and Ophthalmologist should be made aware of the seriousness of the disease and its prevalence in order to encourage them to take precautions when managing other ocular disease to avoid turning a blind eye to the disease. The inclusion of tear osmolarity testing as a tool in assisting with the diagnosis of dry eye syndrome will be recommended for future studies.
Dissertation (M. Optometry (Optometry))--University of the Free State, 2019
Keywords: Prevalence; Dry eye syndrome (DES); Ocular Surface Disease Index (OSDI); Tear-Break Up Time (TBUT); Schirmer 2 Test; Nelson Mandela Academic Hospital (NMAH)